Evaluation of Financial Reporting in Non Profit Organization Under ISAK 335 Case study on Simalungun Protestant Christian Church (GKPS) - Purba, Hans Felix Walker; Wijayati, Nureni (E-Jurnal Akuntansi, 2025)
This study aims to evaluate the financial reporting practices of the Simalungun Protestant Christian Church (GKPS). Employing a single-case study design, the research focuses on a single unit of analysis to provide an in-depth understanding of the church's financial reporting. A qualitative descriptive approach was adopted to comprehend the processes and events occurring in the field, involving interviews with the synod's financial bureau staff and a documentary study of the past year's financial reports. The research also assesses the conformity of the GKPS synod's financial reporting with ISAK 335, the accounting standard for non-profit entities. Findings indicate that the GKPS Synod has not yet implemented ISAK 335 as its accounting standard and has not prepared and published a complete set of financial statements according to ISAK 335. Keywords: Financial Reporting; Non Profit Organizations; ISAK 335; Church Management